2019
DOI: 10.1177/2515135519889000
|View full text |Cite
|
Sign up to set email alerts
|

Active surveillance of adverse events following immunization (AEFI): a prospective 3-year vaccine safety study

Abstract: Background:Vaccines used in national immunization programs are considered safe and effective but immunization safety has become as important as the efficacy of vaccination programs. The objective of the study was to detect adverse events following immunization (AEFIs) to all vaccines administered to a pediatric population in India.Methods:The prospective active vaccine safety surveillance study enrolled eligible children in the age group 0–5 years receiving vaccination from the immunization center at JSS Hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
19
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 16 publications
7
19
2
3
Order By: Relevance
“…In this period of concomitant use, a lower rate of AEFI reports was observed; however, this direct comparison between aP (first and second doses) and wP vaccines (third and booster doses) should be avoided, since clinical trials have shown a higher reactogenicity in the first doses. [15][16][17] Several studies on vaccine hesitancy have shown that the safety profile and AEs can be a barrier and discourage vaccination and increase hesitancy. 18 Various studies, including in Chile, have shown that wP pentavalent vaccines are responsible for most AEFI in children and that the group with the highest frequency of reported AE are infants under 1 year of age, due to the fact that they receive the greatest number of vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…In this period of concomitant use, a lower rate of AEFI reports was observed; however, this direct comparison between aP (first and second doses) and wP vaccines (third and booster doses) should be avoided, since clinical trials have shown a higher reactogenicity in the first doses. [15][16][17] Several studies on vaccine hesitancy have shown that the safety profile and AEs can be a barrier and discourage vaccination and increase hesitancy. 18 Various studies, including in Chile, have shown that wP pentavalent vaccines are responsible for most AEFI in children and that the group with the highest frequency of reported AE are infants under 1 year of age, due to the fact that they receive the greatest number of vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…A alta incidência pode estar associada à imaturidade do sistema imunológico e ao alto número de vacinas administradas nessa faixa etária. (17)(18)(19)(20) Entre os eventos locais e sistêmicos identificados, a dor e a febre foram os mais incidentes. A maioria dos eventos adversos pós-vacinação, locais e sistêmicos, são leves e autolimitantes (8,9,17,21) e representam a área de atuação da equipe de enfermagem, uma vez que, nas unidades de APS públicas brasileiras, ela é a principal responsável pelas atividades de vacinação.…”
Section: Discussionunclassified
“…Profissionais de saúde com conhecimento são capazes de informar os indivíduos sobre a importância e os benefícios da vacinação e sobre os possíveis riscos e a ocorrência de eventos adversos pós-vacinação. (16,20) O fornecimento dessas informações à população, chamado de triagem vacinal, é recomendado como atividade básica a ser realizada nas salas de vacinação. (10) A triagem vacinal é uma medida específica para evitar riscos na vacinação, pois, além de permitir o monitoramento do status vacinal dos indivíduos e de seus históricos de saúde, é quando o profissional de saúde tem a oportunidade de realizar aconselhamentos sobre as vacinas e seus possíveis EAPV.…”
Section: Discussionunclassified
“…The MR vaccine used in the immunization programs (prequalified by WHO) is a live-attenuated vaccine containing the Edmonston strain of measles and the RA 27/3 strain of rubella [17]. Prospective studies that used a similar product found incidence ranging from 13.7% to 20.8% [18,19]. However, one used a smaller sample size of 278 [18], and the other was conducted over a period of three years [19].…”
Section: Discussionmentioning
confidence: 99%
“…Prospective studies that used a similar product found incidence ranging from 13.7% to 20.8% [18,19]. However, one used a smaller sample size of 278 [18], and the other was conducted over a period of three years [19].…”
Section: Discussionmentioning
confidence: 99%